The in vitro apoptotic effect of new zinc complex possessing folic acid and phenanthroline on cervix cancer cells. (28th November 2021) - Yang, Liyun; Heidari Majd, Mostafa; Shiri, Fereshteh; Shahraki, Somaye; Karimi, Pouya
Abstract: With proper care and nursing as well as timely diagnosis and good treatment, cervical cancer is one of the most treatable forms of cancer. One of the most important cancer treatments is the use of emerging developing metal–organic complexes, which can provide a wide variety of morphologies, sizes, and properties based on different metal ions and different organic ligands. Accordingly, we reported the synthesis method, structural properties, cytotoxicity, apoptotic properties, and molecular docking analysis of the new Zn(II) complex consisting of phenanthroline and folic acid ligands. FTIR, 1 H‐NMR, 13 C‐NMR, and elemental analyzer determined that the synthesis of the complex was successful. The IC50 values (380 and 199 μM) were shown that the viability of HeLa cells was dependent on time of exposure and concentration of [Zn(Phen)FA] complex. Real‐time PCR clearly shows increased expression of apoptotic genes in cervical carcinoma HeLa cells and a possible relationship between Bak1/Bclx ratio and caspase‐3. Also, the key amino acids of folate receptor that can interact with the synthesized complex were identified by molecular docking analysis. Moreover, molecular electrostatic potential confirmed that carboxylate portion of FA is an electron‐rich region and can interact with Zn(Phen) to form a stable and soluble complex. All experiments confirmed that presence of FA could improve stability, cytotoxicity, apoptosis, and cellular uptake of complex in cervical carcinoma HeLa cells. Abstract : The cytotoxic effect of [Zn(Phen)FA] complex in HeLa cell lines showed cell viability depended on time and concentration. The real‐time PCR well indicated that the presence of folic acid in the metal complex could activate the mitochondrial pathway of apoptosis in HeLa cells. Based on molecular docking analyses, the key amino acids of the folate receptor for interaction with the synthesized complex were detected.